Sinergitas Pemilihan Presiden 2009 dengan Sistem Presidensialisme Murni dan Konsolidasi Demokrasi di Indonesia - Agus Riewanto (Unisia, 2008)
2009 is the second period of Direct Presidential Election after the first election in 2004.The Presidential Election of 2004 was considered as the eve of the new constitutionalhistory of Indonesia, because by the direct election would strengthen pure presidentialsystem based on the Constitution of 1945 post amendment, and at the same time wouldalso consolidate democracy. In fact, however, during his tenure, the Elect President andhis presidential institution have been facing strong current resistance in the Parliament,and this has been weakening consolidation of democracy. The main cause is the presenceof multiparty which is not compatible with the pure system of presidential, in whichpresident should be stronger or at least balanced with the position of parliament. Thus,Indonesian practice of constitutionalism since 2004 has been reflecting a parliamentarysystem. The Presidential Election of 2009 should synergetic with the pure presidential,and at once end the transition of democracy toward the consolidation of democracy.Keywords: direct election, presidential, consolidate, democracy.